Once Found, What Next?: A Study of 'Keeping' Behaviors in the Personal Use of Web Information - Jones, William; Dumais, Susan; Bruce, Harry (Proceedings of ASIST 2002, 2002)
This observational study investigates the methods people use in their workplace to organize web information for re-use. In addition to the bookmarking and history list tools provided by web browsers, people observed in our study used a variety of other methods and associated tools. For example, several participants emailed web addresses (URLs) along with comments to themselves and to others. Other methods observed included printing out web pages, saving web pages to the hard drive, pasting the address for a web page into a document and pasting the address into a personal web site. Differences emerged between people according to their workplace role and their relationship to the information they were gathering. Managers, for example, depended heavily on email to gather and disseminate information and did relatively little direct exploration of the Web. A functional analysis helps to explain differences in “keeping” behavior between people and to explain the overall diversity of methods observed. People differ in the functions they require according to their workplace role and the tasks they must perform; methods vary widely in the functions they provide. The functional analysis can also help to assess the likely success of various tools, current and proposed.